Motivation as a Constituent Element of Human Psyche - Sabadukha, Oleksii (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2022)
The article examines the fundamental influence of human motivation on human inner and outer worlds. The views of Aristotle were used as the methodological basis to study the causality of the existence of things and phenomena, and as the theoretical basis Kurt Lewin’s psychological field theory was used. The main ways of forming motivation, specifically, the upbringing process and assimilation to the social mechanism of livelihood (the relations of distribution, exchange and ownership) were researched. The connection between motivations, attitudes and dominance has been established. It is proved that motivations form a certain hierarchy of attitudes that are fixed in the human brain as dominants. The influence of motivation on the formation of human typology has been studied: dependent personality, mediocre personality, mature personality and a genius. It has been substantiated that a person of a dependent spiritual development is motivated by immediate needs, the intentions of their consciousness are directed to his body and relations of distribution, and the attitude is a stimulus. The life of a dependent person is focused on pleasure, the dominant is in the area of the striatum; behavior is dominated by the simplest forms of adaptation (stimulus - reaction), and language during communication reflects the bodily needs and desires for satisfaction. It has been further examined that a person of mediocre (reproductive) level of spiritual development is motivated by success, the intentions of his consciousness are directed to his ego, cognition of exchange relations, and attitude is the motive. The life of a mediocre person is built on the principle of reality, and the dominant migrates from the striatum to the prefrontal cortex. Behavior reproduces typical forms of behavior, and language reflects the desire for profit (economic, political, legal, psychological, ideological). It has been concluded that a person of a personal level of spiritual development is motivated by the needs of society, the intentions of their consciousness are aimed at mastering the laws of society, morality, holistic knowledge of relations of distribution, exchange and property, and interest is the attitude. The person’s life is governed by duty, and the dominant is mainly in the prefrontal cortex. Behavior patterns of a mature person are focused on asserting the interests of society, and language reflects the interests of society, its values, goals and national security. Finally, it has been proved that a person of genius level of spiritual development is motivated by the need of finding the truth, the intentions of their consciousness are aimed at mastering the metaphysical laws of existence, and the ideal is the main attitude. The life of a genius is focused on creativity, the dominant is stably in the prefrontal cortex. In behavior, genius is focused on the establishment of ideals, and language reflects the ideals as a combination of Truth, Goodness and Beauty.